HISTOLOGICAL ANALYSIS OF IN VITRO REGENERATION OF HUMAN DENTAL PULP COMPLEX WITH AUTOLOGOUS TISSULAR ENGINEERING - Romero Márquez, Ricardo Manuel (2004)
A long time ago, dental pulp-complex regeneration was our main objective in radicular reparation which could guarantee all appropiate growth of healthy and functional tissue. The present study is about a histological assay of a new dentinal-pulp complex formation using platelet rich plasm, pulpar tissue and fibrina, all autolougus, as components of dental pulp tissular engineering treatment. Qualitative and quantitative assays about the dentin pulp-complex regeneration grade on experimental and control groups were made and showed similar results. This technique opens a pathway for regenerate a complete tooth in the future.